Upaya Peralihan Pengelolaan Air Traffic Controller Dari PT. Angkasa Pura ke Pemerintah - Ismail Najamuddin (Research and Development Agency of The Ministry of Transportation, 2011)
The formation or mangement transition of Air Traffic Control or Air Traffic Services (ATC/ ATS) policy in reference to the Law Number 1 of Year 2009 on Aviation, in article 271 paragraph (1) and (2) and (4), international regulation of ICAO Document 9 191 / 3 Manual on Air Navigation Services Economy as well as other related regulations and policies in participating the increase of aviation safety and service quality, Air Traffic Services performance and Airport Service in entire national air space. In order to make transition formation of Air Traffic Control/Air Traffic Services management to the goverment, it is necessary to do steps to review some aspects as follow : legal/regilation aspect, institutional/organization al aspect and operational/service aspect. Management of Air Traffic Control/Air Traffic Services (ATC/ATS) has to be caharacterized as public services, reducing bureaucracy, integrated service, non-profit oriented and financially independent and organizationally effective and efficient in atool to create unity and entity as well as state's security. The unitary Stafe of Republic of Indonesia has be run by the goverment nationally in a single container.